Statin in the treatment of patients with myocardial infarction: A meta-analysis - Han, Xue (Medicine (Baltimore), 2018)
The purpose of this meta-analysis is to investigate whether statin is a key therapy for myocardial infarction (MI) by comparing all randomized controlled trials that appraised the effects of statin on risk of MI. Pubmed, Embase, and Medline databases (up to December 2016) were used to search all related articles. Using the data from 18 available publications, we examined the efficacy in treating or reducing the risk of MI by using random-effects models of odds ratio (OR) comparing the highest with the lowest category. Statins have demonstrated efficacy in treating or reducing the risk of MI (OR = 0.73, 95% confidence interval = 0.58–0.93, P = .010). This meta-analysis suggests that statin have light efficacy in treating or reducing the risk of MI patients.